The global decline in the sensitivity of vegetation productivity to precipitation from 2001 to 2018. (4th September 2022) - Zeng, Xiang; Hu, Zhongmin; Chen, Anping; Yuan, Wenping; Hou, Guolong; Han, Daorui; Liang, Minqi; Di, Kai; Cao, Ruochen; Luo, Dengnan
Abstract: The sensitivity of vegetation productivity to precipitation ( S ppt ) is a key metric for understanding the variations in vegetation productivity under changing precipitation and predicting future changes in ecosystem functions. However, a comprehensive assessment of S ppt over all the global land is lacking. Here, we investigated spatial patterns and temporal changes of S ppt across the global land from 2001 to 2018 with multiple streams of satellite observations. We found consistent spatial patterns of S ppt with different satellite products: S ppt was highest in dry regions while low in humid regions. Grassland and shrubland showed the highest S ppt, and evergreen needle‐leaf forest and wetland showed the lowest. Temporally, S ppt showed a generally declining trend over the past two decades ( p < .05), yet with clear spatial heterogeneities. The decline in S ppt was especially noticeable in North America and Europe, likely due to the increase in precipitation. In central Russia and Australia, however, S ppt showed an increasing trend. Biome‐wise, most ecosystem types exhibited significant decrease in S ppt, while grassland, evergreen broadleaf forest, and mixed forest showed slight increases or non‐significant changes in S ppt . Our finding of the overall decline in S ppt implies a potential stabilization mechanism for ecosystem productivity under climate change. However, the revealed S ppt increase for some regions and ecosystem types, in particular global grasslands, suggests that grasslands might be increasingly vulnerable to climatic variability with continuing global climate change. Abstract : We combined multiple satellite products and land models to assess the spatial patterns and temporal trends of sensitivity of vegetation productivity to precipitation. Our results suggest that precipitation sensitivity varied greatly across the globe, with high values in arid regions and low in mesic regions. Furthermore, the overall global precipitation sensitivity has decreased significantly over the past two decades, which is mainly due to the increase in precipitation. If this trend continues, the negative impacts of global changes on vegetation productivity stability in terrestrial ecosystems may be mitigated to some extent.